O filosofar e o uso do livro didático de Filosofia : uma perspectiva em sala de aula - Monteiro, Ezequiel Matos (2021)
Philosophy teaching in high school is a philosophical problem that can be summed up in the following question: what is teaching philosophy in high school? Thus, the central theme is philosophy teaching. In face of the generality of this problem, we choose to research teaching from another question: is it possible to philosophize using textbooks as a resource? The search for this answer finds its justification in Philosophy teaching, which in the majority of cases is constituted by a small quantity of philosophy classes, which results in more groups of students, students, and bureaucracy. The intention is to teach philosophy supported by the philosophizing act, and using Philosophy textbook, available in public school. To answer the question, a theoretical framework is composed defining what is to philosophize, in which epistemological and didactical concepts are presented, as well as a discussion about the Base Nacional Curricular Comum, in the first chapter. In the second chapter, the use of philosophical textbooks in order to teach philosophy is justified as a feasible option. In the third chapter there is the lesson plan's elaboration, and in the last one there is a report about the classes that were teaching and the reflections about the encounter between theoretical foundation and teaching practice. Philosophize's initial concept is extracted from Ghedin (2009) and faces a ponderation throughout the research. Philosophize reflection is brought to pandemic context (2020-2021), promoting a discussion about the impact of this health crisis to education.